Voices of Resistance : Communication and Social Change - Dutta, Mohan J. (Book collections on Project MUSE., 2012)
This book re-presents voices of resistance from across the globe to document the communicative processes, practices, and frameworks through which neoliberal global policies are currently being defied. Based on examples, case studies, and ethnographic reports, Voices of Resistance serves as a space for engaging various perspectives from the global margins in dialogue. The emphasis of the book is on the core idea that creating spaces for listening to voices of resistance fosters openings for the politics of social change?interweaving the stories of the local, the national, and the global. The book is divided into chapters addressing the politics of resistance in the contexts of global economic policies, agriculture, education, health, poverty, and development.